869 * .08 = 69.52
69.52 + 869 = 938.52
938.52- 75 = 863.52
Answer:
the solution of the system is:
x = 1 and y = 2.
Step-by-step explanation:
I suppose that we want to solve the equation:
-6*x + 6*y = 6
6*x + 3*y = 12
To solve this, we first need to isolate one of the variables in one of the equations.
Let's isolate y in the first equation:
6*y = 6 + 6*x
y = (6 + 6*x)/6
y = 6/6 + (6*x)/6
y = 1 + x
Now we can replace this in the other equation:
6*x + 3*(1 + x) = 12
6*x + 3 + 3*x = 12
9*x + 3 = 12
9*x = 12 - 3 = 9
x = 9/9 = 1
Now that we know that x = 1, we can replace this in the equation "y = 1 + x" to find the value of y.
y = 1 + (1) = 2
Then the solution of the system is:
x = 1 and y = 2.
Closed dot on 53, arrow going to the right
<u>Answer</u>
26.6°
<u>Explanation</u>
You are required to use the trigonometric ratio, sine, to find that angle.
SinФ = opposite/hypotenuse
sin Θ = 2.6/5.8
= 0.4483
The angle Θ = Anti-sine(0.4483)
= 26.633°
The angle the slide makes with the ground, correct to one decimal place is 26.6°